Electronic Governance: Improving Service Delivery in Nigeria - Oloyede, Funmilayo (PERSPEKTIF, 2024)
The objective of this study is to find out the impact of technology on the e-governance of Nigeria, examine e-governance and its implementation, and identify the challenges of e-governance in the State. A qualitative research method was adopted and the study made use of ex-post facto secondary data which involved an extensive literature review of related articles in journals. The study found that there have been notable improvements due to the application of e-governance in the daily transactions in Nigeria, especially, in the areas of communication, health, education, and banking system, yet there are flaws identified, such as inadequacy in the procedure for Information and Communication Technology (ICT) regulatory structure, problems of the corrupt bureaucrats who use their power to frustrate the effective application of e-governance, also the constant interruption of internet caused by unstable electricity. These have reduced the expected achievement, and unsatisfactory service delivery most times. This paper concludes that the Nigerian government must address obstacles hindering e-governance through ICTs. Improving government involvement in e-governance through the use of Information and Communication Technologies (ICTs) is crucial because efficient and accelerated service delivery requires pure technology and citizen feedback channels. Also, Government policy on e-governance must remain rigid to prevent corrupt bureaucrats from limiting the system.